2012
DOI: 10.4314/ajpsy.v15i3.21
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Services in South Africa: Scaling up and future directions

Abstract: Abstract"No health without mental health" has become a rallying call for the World Health Organization and numerous service providers, training institutions, health researchers, and advocacy groups around the world. It is timely to consider the implications of this call for South Africa. We review key evidence regarding the burden and risk factors for mental disorders in South Africa and crucial challenges for local mental health services and research. We emphasize that mental disorders are more impairing but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 44 publications
(40 reference statements)
1
24
0
Order By: Relevance
“…Mental disorders are often under-diagnosed (Jonsson et al, 2013;Sorsdahl et al, 2012). Since patients are unlikely to disclose their mental state, Jonsson and colleagues recommend that patients on ART be screened using the three questions in the recently published clinical guideline "Management of mental health disorders in HIV-positive patients receiving ART" (Jonsson et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mental disorders are often under-diagnosed (Jonsson et al, 2013;Sorsdahl et al, 2012). Since patients are unlikely to disclose their mental state, Jonsson and colleagues recommend that patients on ART be screened using the three questions in the recently published clinical guideline "Management of mental health disorders in HIV-positive patients receiving ART" (Jonsson et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…An additional 361 psychiatrists, 135 nurses and 2937 psychological care providers, which include psychologists and social workers, are needed to meet the mental health demands of South Africans (Day, Gray, & Budgell, 2011). Patient factors associated with low detection and treatment of mental disorders are poor mental health literacy and stigma associated with mental disorders (Sorsdahl, Stein, & Lund, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Physically, some of them are very untidy and indecent. In the view of Sorsdahl et al (2012), "[c]ompared to an average person, those with a mental disorder are viewed as being more unpredictable, tense and dangerous, worthless, delicate, slow, weak, dirty, and foolish" (p.169). They therefore become people who are dreaded and cannot be apprehended by just one person.…”
Section: Idioms and Proverbsmentioning
confidence: 99%
“…Various South African studies on mental disorders have demonstrated the high prevalence and morbidity of mental health conditions (Sorsdahl et al, 2012) in addition to the lack of professionals available to deal with this situation (Petersen, 2004). Sorsdahl et al (2012) noted that there is staggering evidence for the efficacy and cost-effectiveness of psychotherapeutic interventions for mental disorders.…”
Section: Theme 2: Perception Of the Role Of Registered Counsellors Inmentioning
confidence: 99%
“…Sorsdahl et al (2012) noted that there is staggering evidence for the efficacy and cost-effectiveness of psychotherapeutic interventions for mental disorders. Kotze and Carolissen's (2005) research suggested that psychologists and psychiatrists were mainly serving the private sector and that it was therefore necessary to develop counsellors within the HPCSA to provide valuable mental health-care services at a primary level.…”
Section: Theme 2: Perception Of the Role Of Registered Counsellors Inmentioning
confidence: 99%